Estudo comparativo dos tratamentos fisioterapêuticos e psicológicos em pacientes atendidas no setor de sexualidade feminina - Projeto Afrodite da Disciplina de Ginecologia endocrinológica da Universidade Federal de São Paulo - Alcides, Maria Angelica [UNIFESP] (2013)
Objetive: To evaluate and compare the proposed physiotherapeutic and psychotherapeutic interventions in patients with the diagnosis of vaginismus. Methods: We evaluated and compared in a descriptive study with 24 women, two groups: physiotherapy treatment (G1) and psychological treatment and physiotherapy (G2). Both groups underwent screening and were assessed through evaluation form by the multidisciplinary team (Doctors, Psychologists, Physiotherapists) sector of female sexuality Unifesp. To evaluate the physical therapy evaluation was performed bodily and physical assessment of pelvic floor muscle using palpation method and perineal body (subjective) so we could see any changes involuntary spastic contraction. We evaluated the physical and functional integrity of the pelvic floor in order to assess possible changes in muscle through digital examination and/or bidigital (objective evaluation). Were also collected during the evaluation questionnaires Sexual Quality of Life ? Female Sexual Quotient and Inventory and Beck ? BDI (psychological evaluation) for both the G1 Group as well as for the Group G2. Only underwent the treatment, patients with diagnosis of vaginismus. After signing the consent form, the same was referred for treatment with physical therapy and psychology individualized treatments. The number of sessions for therapy (physiotherapy and psychological) were 10 initial sessions the treatment may be extended for 10 more sessions if the multidisciplinary team thought very necessary. The treatment group G1 and G2 were started by working sex education (through the mirror technique and illustrative booklet (anatomy of the internal and external genitalia). Treatment Group G1 was accomplished through relaxation techniques and perineal body, respiratory training, normalization of body tone and perineal massage performed with and desensitization and perineal body and application of specific exercises (body awareness ? and acceptance verbalization through visualization and perineal body in the mirror) (mirror technique ? visualization body) and (autofocus ? visual and tactile perception of the body in the mirror). Results: The study included 15 patients in Group G1 and 9 patients in Group G2. With respect to gynecological assessment, initially seventeen (70.83%) failed to perform evaluation at the end of treatment the twenty-for (100.0%) have done it. In assessing physiotherapy, seven (46.67%) and nine in Group G1 (100.0%) in Group G2 conducted subjective evaluation and eight (53.33%) underwent objective evaluation the end of treatment the twenty-four (100.0%) of the patients began to perform objective evaluation. There was also improvement in relation to the scores of QSF (Female Sexual Quotient) and BDI (Beck Inventory of Psychological Assessment) and regarding the Partial and Total Penetration. Conclusions: physiotherapy should be an integral part of the multidisciplinary team treating sexual dysfunctions, we conclude also that the resources physiotherapeutic help produce physical changes in the body and perineal muscle, central nervous system, altering the mechanism of pain through the reeducation sensory motor.